Data Mining Application Based on Cloud Model in Spatial Decision Support System - Hong-li Wang; Li Meng; Mu-kun Cao; Yan Li (2008 ISECS International Colloquium on Computing, Communication, Control, and Management, 2008)
It is a key problem to represent properly the knowledge in space decision support system. The knowledge has the character of multi-dimension, fuzzy and randomcity in uncertain problems on space decision. In order to improve the ability of dealing with uncertain problems in space decision support system the representation and induction based on cloud model is proposed in this article. Firstly the multi-dimension cloud model is given to represent the knowledge stored in knowledge database in space decision support system. Then knowledge induction method based on multi-dimension cloud model is proposed. Lastly a case in space environment decision is given to verify the methodpsilas validity. Contrast to previous method, the innovation of method is that the complete knowledge representation and induction based on cloud model with the merit of representing multi-dimension, fuzzy and random knowledge is given.